EARLY MARKERS OF DIABETIC NEPHROPATHY IN CHILDREN WITH TYPE 1 DIABETES MELLITUS - Аkhmadov, G.A. (World of Medicine and Biology, 2022)
The purpose of the study was to reveal the markers for timely detection of diabetic nephropathy in children with type 1 diabetes mellitus. 54 children with type 1 diabetes mellitus were examined (mean age: 13.76±4.5 years; diseases duration: 5.68±3.7 years). Blood glucose, glycohemoglobin, blood urea, general analysis of urine, calcium, creatinine, protein, glucose in the urine and microalbuminuria were determined by laboratory tests. Conditions of kidney and liver were access by abdomen ultrasound. Results showed that in children with type 1 diabetes mellitus there was a positive correlation between microalbuminuria and disease duration (r=+0.383, p=0.036), urine glucose and the width of the right (r=+0.82, p
Keywords: type 1 diabetes mellitus; diabetic kidney disease; microalbuminuria; risk factors